Making the cut: intramembrane cleavage by a rhomboid protease promotes ERAD - Greenblatt, Ethan J (2012)
Endoplasmic reticulum–associated degradation (ERAD) is a cellular protein quality-control process that disposes of proteasomal substrates from the early secretory pathway. Recent work shows that the endoplasmic reticulum–resident rhomboid protease RHBDL4 facilitates ERAD by recognizing and cleaving integral membrane substrates. The work indicates that intramembrane proteolysis may have a general role in the extraction of misfolded membrane proteins from the endoplasmic reticulum.